2021
DOI: 10.1002/anie.202111076
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Studies of Phomopsins Unveil Posttranslational Installation of Dehydroamino Acids by UstYa Family Proteins

Abstract: UstYa family proteins (DUF3328) are widely and specifically distributed in fungi. They are known to be involved in the biosynthesis of ribosomally synthesized and posttranslationally modified peptides (RiPPs) and nonribosomal peptides, and possibly catalyze various reactions, including oxidative cyclization and chlorination. In this study, we focused on phomopsin A, a fungal RiPP consisting of unique nonproteinogenic amino acids. Gene knockout experiments demonstrated that three UstYa homologues, phomYc, phomY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…29,30 The three families are XyeB (TIGR04496, IPR030989), GrrM (TIGR04261, IPR026357), and FxsB (TIGR04269, IPR026335). 27 In our initial report, we functionally validated and characterized the enzyme product of 17 and AprY 16 are suspected to be involved in the cyclization of phomopsin A and asperipin-2a, respectively. Plant cyclopeptide alkaloids are represented by paliurine F and selanine A and are biosynthesized by Cu-dependent BURP domain proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 The three families are XyeB (TIGR04496, IPR030989), GrrM (TIGR04261, IPR026357), and FxsB (TIGR04269, IPR026335). 27 In our initial report, we functionally validated and characterized the enzyme product of 17 and AprY 16 are suspected to be involved in the cyclization of phomopsin A and asperipin-2a, respectively. Plant cyclopeptide alkaloids are represented by paliurine F and selanine A and are biosynthesized by Cu-dependent BURP domain proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The former is responsible for the pathogenesis in the host organism and has shown potent antimitotic activity . The biosynthetic gene clusters (BGCs) for phomopsins and other dikaritin natural products have been identified, and the enzymes responsible for the macrocyclization are suspected to be DUF3328 proteins. , A second source is termed cyclopeptide alkaloids from plants. These comprise >200 structures that have been characterized and have a range of biological activities (sedative, antibacterial, antifungal, and antiplasmodial effects) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Whilst the power of P450s as biocatalysts is apparent, a challenge to their application in peptide crosslinking is that many pathways in which they occur are non-ribosomal and are difficult to engineer or exploit for synthesis due to their challenging (typically enzyme bound) substrates. [9] Ribosomal (RiPP) pathways offer greater potential to identify P450 (and other) [10] enzymes as biocatalysts due to their simpler substrates, [11] although these can still be long peptides due to the large leader sequences required for cyclisation (as seen in darobactin and cittilin). [12] Given this, we focussed on the biarylitides, a class of RiPPs that contain YxH tricyclic motifs installed by P450s.…”
mentioning
confidence: 99%
“…Gene knockout experiments have shown that three UstYa family proteins, phomYc , phomYd and phomYe are required for the desaturation of amino acid moieties of phomopsin A 37 , a mycotoxin produced by the fungal pathogen Phomopsis leptostromiformis . 29 Bioinformatic analysis revealed that the UstYa family contains a variety of proteins with unknown function, that have the potential to be used as genome mining probes for the discovery of novel fungal metabolites. Directed evolution has been used to redesign 2-deoxy- d -ribose-5-phosphate aldolase (DERA) from Escherichia coli as an effective biocatalyst for the enantioselective Michael addition of nitromethane to α,β-unsaturated aldehydes.…”
mentioning
confidence: 99%